Komunikasi Dalam Ilmu Akuntansi - Triseptya, Ghaliyah Nimassita (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
This study aims to determine the importance of communication knowledge in its application in accounting science. The data of this study were obtained from interviews with 3 respondents who have worked in the accounting-related divisions. Samples were obtained using simple random sampling. The results of this study indicate that accounting and communication science are closely related. Because in order to obtain reliable financial statements and communicate the state of the financial position, matters relating to its preparation are expected to be communicated properly. Therefore, accounting science and communication science have a great relationship, both verbally and non-verbally.